2022
DOI: 10.1149/1945-7111/ac8a1a
|View full text |Cite
|
Sign up to set email alerts
|

Improved Particle Swarm Optimization-Extreme Learning Machine Modeling Strategies for the Accurate Lithium-ion Battery State of Health Estimation and High-adaptability Remaining Useful Life Prediction

Abstract: To ensure the secure and stable operation of lithium-ion batteries, the state of health (SOH) and the remaining useful life (RUL) are the critical state parameters which must be estimated precisely. Here, a joint SOH and RUL estimation approach based on an improved particle swarm optimization extreme learning machine (PSO-ELM) is proposed. The approach adopts Pearson coefficients to screen multivariate information of the discharge process as health indicators and uses them as inputs to enable accurate estimati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…There are two main common SOH estimation methods, one is based on an electrochemical model or equivalent circuit model, and the other is based on a data-driven approach. [12][13][14] The method based on the electrochemical model or equivalent circuit model uses the parameters identified by the model to calibrate the SOH of the lithium-ion battery. At the same time, some scholars combine parameter identification and filtering algorithms to complete SOH estimation.…”
mentioning
confidence: 99%
“…There are two main common SOH estimation methods, one is based on an electrochemical model or equivalent circuit model, and the other is based on a data-driven approach. [12][13][14] The method based on the electrochemical model or equivalent circuit model uses the parameters identified by the model to calibrate the SOH of the lithium-ion battery. At the same time, some scholars combine parameter identification and filtering algorithms to complete SOH estimation.…”
mentioning
confidence: 99%
“…[23][24][25][26][27] Moreover, the state of power (SOP) and the state of health (SOH) of the battery are also associated with the SOC. [28][29][30][31][32][33][34][35][36][37][38] Therefore, OCV identification is the basis for accurate estimation of SOC, SOP, and SOH.…”
mentioning
confidence: 99%
“…It can be found that the increase of the feature input dimension will lead to a surge in the amount of calculation of the model, resulting in more abnormal noise, and overfitting. Researchers adjust the model through transfer learning, particle swarm optimization (PSO), 23,24 and other methods to improve the performance of the model, while improving the accuracy and robustness of the model. For example, ZHANG et al 24 predicted SOH and RUL on the PSO optimized extreme learning machine (ELM) based on multivariate information during the discharge process as input.…”
mentioning
confidence: 99%
“…Researchers adjust the model through transfer learning, particle swarm optimization (PSO), 23,24 and other methods to improve the performance of the model, while improving the accuracy and robustness of the model. For example, ZHANG et al 24 predicted SOH and RUL on the PSO optimized extreme learning machine (ELM) based on multivariate information during the discharge process as input. The optimized model proposed estimates the SOH and RUL with relatively high accuracy.…”
mentioning
confidence: 99%